The Role of Academic Buoyancy and Social Support in Mediating Associations Between Academic Stress and School Engagement in Finnish Primary School Children - Piia af Ursin; Tero Järvinen; Päivi Pihlaja (Routledge, Taylor & Francis Group, 2026)
School engagement is critical to learning and long-term academic success. Feeling overwhelmed with school demands form a threat to students’ engagement. We examined the roles of person-internal (academic buoyancy) and person-external (social support) factors in mediating the association between academic stress and school engagement among primary school children in Finland. A sample of 403 children aged 8–9 years participated in this study. Analysis using structural equation modeling revealed that academic stress is negatively associated with engagement. The effect of academic stress on cognitive engagement was fully mediated by academic buoyancy and social support, whereas the effect on emotional engagement was partially mediated by these. Results suggest that supporting children’s ability to deal with setbacks, providing social support, and promoting a socially supportive climate could be effective for the prevention of stress and its negative association with school engagement.